A Framework for Untangling Transient Groundwater Mixing and Travel Times. Issue 4 (7th April 2021) - Popp, Andrea L.; Pardo‐Álvarez, Álvaro; Schilling, Oliver S.; Scheidegger, Andreas; Musy, Stéphanie; Peel, Morgan; Brunner, Philip; Purtschert, Roland; Hunkeler, Daniel; Kipfer, Rolf
Abstract: Understanding the mixing between surface water and groundwater as well as groundwater travel times in vulnerable aquifers is crucial to sustaining a safe water supply. Age dating tracers used to infer apparent travel times typically refer to the entire groundwater sample. A groundwater sample, however, consists of a mixture of waters with a distribution of travel times. Age dating tracers only reflect the proportion of the water that is under the dating range of the used tracer, thus their interpretation is typically biased. Additionally, end‐member mixing models are subject to various sources of uncertainties, which are typically neglected. In this study, we introduce a new framework that untangles groundwater mixing ratios and travel times using a novel combination of in‐situ noble gas analyses. We applied this approach during a groundwater pumping test carried out in a pre‐alpine Swiss valley. First, we calculated transient mixing ratios between recently infiltrated river water and regional groundwater present in a wellfield, using helium‐4 concentrations combined with a Bayesian end‐member mixing model. Having identified the groundwater fraction of recently infiltrated river water ( F rw ) consequently allowed us to infer the travel times from the river to the wellfield, estimated based on radon‐222 activities of F rw . Furthermore, we compared tracer‐based estimates of F rw with results from a calibrated numerical model. We demonstrate (i) that partitioning of major water sources enables a meaningful interpretation of an age dating tracer of the water fraction of interest and (ii) that the streambed has a major control on the estimated travel times. Key Points: We introduce a framework to estimate mean travel times of a groundwater fraction consisting of recently infiltrated river water ( F rw ) We test the influence of temporally variable end‐member tracer concentrations on estimated mixing ratios We demonstrate that the streambed has a major control on the travel times of F rw